Wie China internen und externen wirtschaftlichen Herausforderungen begegnen will - Frank Bickenbach; Wan-Hsin Liu (Wirtschaftsdienst, 2023)
The mounting economic and technological conflict with the U.S. is hitting China's economy at a difficult time. Harsh retaliation by China against U.S. economic sanctions would further exacerbate its internal economic problems. During the 2023 National People's Congress, the Chinese leadership has made it clear that it is currently giving priority to addressing its internal economic problems. At the same time, it is also stepping up eff orts to enhance the security of China's industrial and supply chains and its self-reliance in science and technology. This reduces China's vulnerability in the conflict with the U.S. and strengthens its capacity for future countermeasures.
Keywords: F23; F52; L50; 330